Dari Konsep ke Realisasi: Pemberdayaan Siswa SMK melalui Workshop Pembuatan Filter Air sebagai Teknologi Tepat Guna - Warit Abi Nurazaq; Audha Fitrah Aulina; Reynaldi Akbar Ali; Haning Hasbiyati; Novangga Adi Mulyono (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Access to safe and clean water remains a critical challenge in many educational institutions and local communities, particularly those relying on groundwater sources without adequate treatment. This community service program aimed to enhance students’ knowledge, technical skills, and environmental awareness through a workshop on constructing simple water filtration systems using locally available materials. The activity was conducted at SMK Darul Hikmah Kranjingan using a project-based learning approach that combined 20% theoretical instruction and 80% hands-on practice. Evaluation was carried out through pre- and post-activity surveys covering cognitive, psychomotor, and affective domains. The results indicate a substantial improvement in student competencies, where more than 60% of students reached moderate to very good levels of understanding in the cognitive domain, 70–80% demonstrated basic technical skills in assembling water filters, and over 90% showed positive attitudes toward clean water and sanitation. The constructed filter prototypes functioned effectively in improving water clarity based on visual observation. Overall, this program demonstrates that practice-based learning in community service activities is effective in strengthening vocational skills, improving water literacy, and fostering responsible water use behavior. The program contributes directly to the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 6 (Clean Water and Sanitation), and SDG 12 (Responsible Consumption and Production).